Cytosolic 5′‐Nucleotidase 1A As a Target of Circulating Autoantibodies in Autoimmune Diseases. Issue 1 (January 2016) - Lloyd, Thomas E.; Christopher‐Stine, Lisa; Pinal‐Fernandez, Iago; Tiniakou, Eleni; Petri, Michelle; Baer, Alan; Danoff, Sonye K.; Pak, Katherine; Casciola‐Rosen, Livia A.; Mammen, Andrew L.
Abstract : Objective: Prior investigations demonstrated that autoantibodies recognizing cytosolic 5′‐nucleotidase 1A (NT5C1A) are found in 33–76% of patients with inclusion body myositis (IBM) but are observed only rarely in patients with polymyositis (PM). Thus, anti‐NT5C1A may help distinguish IBM from PM. Although 4–21% of patients with dermatomyositis (DM) were shown to be anti‐NT5C1A antibody positive, the clinical features of anti‐NT5C1A–positive patients with DM have not been described. Furthermore, the prevalence of anti‐NT5C1A antibodies in other rheumatic conditions has not been reported. This study was undertaken to define the prevalence and clinical features of anti‐NT5C1A–positive patients with DM, PM, IBM, or other systemic autoimmune diseases. Methods: We screened for anti‐NT5C1A autoantibodies in patients with IBM, DM, PM, Sjögren's syndrome (SS), or systemic lupus erythematosus (SLE) and in healthy volunteers. Clinical characteristics were compared between patients who were anti‐NT5C1A positive and those who were anti‐NT5C1A negative. Results: Anti‐NT5C1A autoantibodies were detected in 71 (61%) of 117 patients with IBM, 2 (5%) of 42 patients with PM, 2 (5%) of 42 healthy volunteers, 24 (15%) of 159 patients with DM, 10 (23%) of 44 patients with SS, and 13 (14%) of 96 patients with SLE. No anti‐NT5C1A antibody–positive patients with SS or SLE had muscle involvement. Anti‐NT5C1A–positive patients with IBM had a lower prevalence of rimmed vacuoles (62% versus 83% of antibody‐negative patients; P = 0.02). No differences in the clinical characteristics of antibody‐positive and antibody‐negative patients with DM, SS, or SLE were observed. Conclusion: Anti‐NT5C1A is a common target of circulating autoantibodies, especially in IBM but also in several different autoimmune diseases. In SLE and SS, anti‐NT5C1A autoreactivity is not associated with muscle disease.